2009
DOI: 10.1118/1.3263614
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the interplay effect when using RapidArc to treat targets moving in the craniocaudal or right‐left direction

Abstract: The interplay between the motions of the LINAC and the target can result in an error in the delivered dose. This effect increases with plan complexity, and with target magnitude and period. It may average out after many fractions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 21 publications
6
64
0
1
Order By: Relevance
“…This effect has been studied in only two publications for tangential fields techniques39, 40 but not for VMAT for breast. However, the interplay effect has been largely studied in the case of lung RT41, 42, 43, 44, 45, 46 with motion amplitude being largely superior to those encountered in breast treatment. Those studies show that the interplay effect generates a blurring effect on the dose distribution.…”
Section: Discussionmentioning
confidence: 99%
“…This effect has been studied in only two publications for tangential fields techniques39, 40 but not for VMAT for breast. However, the interplay effect has been largely studied in the case of lung RT41, 42, 43, 44, 45, 46 with motion amplitude being largely superior to those encountered in breast treatment. Those studies show that the interplay effect generates a blurring effect on the dose distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Complex treatments (e.g., dose painting 7 ) with inversely optimized arc radiotherapy are generally characterized by highly modulated beams and the interplay between the motion of the tumor and the linac motions during treatment has been shown to give errors in the delivered dose. 8 Gating 9,10 has been used frequently in the last decade for treatment of breast cancer but has limitations in the treatment time efficiency, since the radiation delivery is interrupted when the tumor motion exceeds the predefined range.…”
Section: Discussionmentioning
confidence: 99%
“…(b) Two indices combining the MCSv, amplitude, and NBs were introduced. The magnitude of interplay effect cannot be evaluated from only one factor, because the interplay effect is caused by combination of various factors such as amplitude, breathing cycle, dose rates, and MLC sequence 4, 5, 6. Therefore, the combination of tumor motion and MCSv (TMMCSv) is calculated as the quotient of the MCSv and amplitude.…”
Section: Methodsmentioning
confidence: 99%
“…showed that the maximum dose variation due to the interplay effect can be up to 30% for one intensity modulated radiation therapy (IMRT) field over one fraction, and 18% for all five IMRT fields over one fraction. Court et al 5. showed that dose error could be >5% for the area of 40% in the target when target motion was 2 cm for VMAT plans (2 Gy/1 fraction).…”
Section: Introductionmentioning
confidence: 99%